Samuel Schelguigius S. Theol. D. Et Prof. P. Athenaei Gedanensis Rector Et Ad SS. Trini. Pastor / J. C. B. - Böcklin, Johann Christoph (1657-1709) (1700)
Przedstawia portret w popiersiu Samuel Schelwig (1643-1715).